Body weight perception and depressive symptoms in Chinese college students. (May 2021) - Zhang, Yueyun; Liu, Baozhong
Highlights: We linked weight perception to depressive symptoms in Chinese college students. Overall, perceived overweight was related to significant depressive symptoms. Overall, perceived underweight was related to depressive symptoms only in men. In subsample BMI < 18.5, an over-perception increased depression risks for women. In subsample BMI ≥ 25, perceived normal-weight lowered depression risks for men. Abstract: Depressive disorder among college students is a prominent issue. Recent evidence indicates that body weight perception (BWP) is, in addition to body mass index (BMI), associated with mental health in adolescents. This study used data from a large-scale, national survey of college students in China to examine the overall relationship between BWP and depressive symptoms and its variation across BMI-classified subgroups: the underweight (BMI < 18.5), the normal-weight (18.5 ≤ BMI < 25), and the overweight (BMI ≥ 25). Depressive symptoms were evaluated using a 10-item version of the Center for Epidemiologic Studies-Depression (CES-D). BWP was measured by asking "What do you think of your weight status?" Response options include "underweight", "normal weight", and "overweight". In both the overall sample and the normal-weight subsamples, perceived overweight was linked to significant depressive symptoms for men and women, while perceived underweight was linked to depressive symptoms only in men. In the underweight subsample, perceived normal-weight or overweight was associated with depressive symptoms for women. In the overweight subsample, perceived normal-weight was associated with a lower level of depressive symptoms for men. The results showed the importance of BWP in predicting depressive symptoms of college students. In-campus health education programs tailored to differential BMI and gender groups can be specifically designed to improve the psychological wellbeing of young adults.